Burial practice in contemporary Iceland: Tradition and conflict - Schurack, Silke, 1975- (2014)
Burial options in Western societies are increasing in diversity. Yet, in Iceland, burial culture remains monopolized by the National Church and specialists such as funeral services. Alternative burial practices, as for example natural burials, are entirely absent. The reasons are the consequences of several aspects as will be shown in the following essay by exploring a range of written material from Iceland as well as from other Western societies for comparative purposes. Iceland´s society is demographically rapidly changing and as response to that it is important to open and clarify the current legal framework concerning burial matters. This can be done by increasing awareness through public discourse and loosing the ties between the law and the church in this area.